2019
DOI: 10.1192/bjo.2019.56
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of therapeutic treatment outcome in adolescent chronic tic disorders

Abstract: Background Chronic tic disorders may have a major impact on a child's function. A significant effect has been shown for combined habit reversal training (HRT) and exposure response prevention (ERP) treatment delivered in an individual and group setting. Aims The present study examines predictors and moderators of treatment outcome after an acute therapeutic intervention. Method Fifty-nine children and adolescents were randomised to manualised treatment combining HRT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Using data from a randomized trial evaluating a combination of HRT and ERP (described in more detail in a later section) [ 43 ], Nissen et al investigated possible predictors and moderators of treatment response [ 44 ]. Their data suggest that internalizing symptoms (anxiety) predicted a lesser reduction in functional impairment and that participants’ (negative) beliefs about their tics were shown to have a negative effect on treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Using data from a randomized trial evaluating a combination of HRT and ERP (described in more detail in a later section) [ 43 ], Nissen et al investigated possible predictors and moderators of treatment response [ 44 ]. Their data suggest that internalizing symptoms (anxiety) predicted a lesser reduction in functional impairment and that participants’ (negative) beliefs about their tics were shown to have a negative effect on treatment outcome.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PU plays an important role in the tic generation (Rae et al, 2019 ). This has led some experts to recommend that the PU could be considered as a target symptom in reducing the tic symptoms (Nissen et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Nissen et al [ 19 ] has previously shown that Beliefs About Tics Scale (BATS) [ 21 ] scores at the 8th session moderated the perceived FI [ 19 ]. In the present study, there was a significant positive association between the BATS scores and TTS over the follow-up period also pointing towards an importance of persistent thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a weaker, but positive association was also seen for mood and feelings questionnaire (MFQ) supporting the importance of a child`s mood. When evaluating immediate outcome, we have previously shown that a high scores on the MFQ favoured individual treatment [ 19 ]. The present study suggests, that mood also may influence long-term outcome independently of the setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation